Light and nutrient supply mediate intraspecific variation in the nutrient stoichiometry of juvenile fish. Issue 10 (21st October 2016) - Downs, Kelsea N.; Hayes, Nicole M.; Rock, Amber M.; Vanni, Michael J.; González, María J.
Abstract: Intraspecific variation in the nutrient stoichiometry of animals and their waste products can be substantial, but the factors mediating this variation are unclear. We experimentally manipulated light, nutrient supply, and nutrient ratio (N:P) in a field experiment to generate variation in algal quantity and elemental composition, and assessed the stoichiometric responses of juvenile carnivorous fish (bluegill, Lepomis macrochirus ). Algal quantity (primary production) and stoichiometry (ratios of carbon [C], nitrogen [N], and phosphorus [P]) varied greatly in response to manipulations, as did bluegill body and excretion stoichiometry. Algal primary production (PPr) was greatest at high light and high P supply (HL HP). Algal stoichiometry responded in accordance with the light:nutrient hypothesis; that is, C:P ratios were highest at HL LP and lowest at LL HP. Variation in fish body stoichiometry was strongly related to basal resource supply (PPr), while excretion stoichiometry was driven by both PPr and algal stoichiometry. Bluegill growth and body C and N concentrations were highest at HL HN and lowest at LL LN, whereas body P showed the opposite pattern. Thus, bluegill body C:P, C:N, and N:P were highest under HL HN and lowest under LL LN. Per capita excretion rates of bluegill were strongly related to body mass and hence were highest at HL HN, where fish grew largest. However, P excretion rates normalized for body mass increased with phytoplankton P and zooplankton production. In accordance with ecological stoichiometry theory, N:P excretion ratio increased with basal resource (algal) N:P and decreased with estimated bluegill P ingestion. Variation in both body and excretion stoichiometry in this single cohort of fish was comparable to or exceeded variation observed in other studies of bluegill stoichiometry across multiple ecosystems. Our results illustrate the pronounced intraspecific variation in carnivore nutrient stoichiometry as a function of basal resource quantity and quality.